Creativity on Student’s Entrepreneurial Intention: The Moderating Effect in The Theory of Planned Behavior - Oktaviani, Leny Kurnia; Noviani, Leny (Economic Education and Entrepreneurship Journal, 2024)
The purpose of this research is to determine the effects of Creativity, Entrepreneurial Attitude (EA), Perceived Behavioral Control (PBC), and Subjective Norms (SN) on Entrepreneurial Intention (EI), moderation of creativity in the influence of EA, PBC, and SN on Entrepreneurial Intention (EI), and the effect of Entrepreneurial Self-Efficacy (ESE) on PBC in active students at Sebelas Maret University, Surakarta. This research is quantitative. The sample in this research consisted of 381 active students at Sebelas Maret University, Surakarta, who were currently taking or had previously taken entrepreneurship courses. Data collection was conducted using a questionnaire distributed via Google Forms. Primary data were analyzed using Structural Equation Modeling (SEM). The results show that Creativity, EA, PBC, and SN positively and significantly affect EI. Creativity can strengthen the effect of PBC on EI. However, not on EA and SN, and ESE has a positive and significant effect on PBC in students at Sebelas Maret University, Surakarta. Entrepreneurship education implemented in higher education should focus on developing the three components of the Theory of Planned Behavior and student creativity.DOI: http://dx.doi.org/10.23960/E3J/v7.i2.251-259